2018
DOI: 10.1101/346759
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensitive periods for white matter plasticity and reading intervention

Abstract: As a child matures, some brain circuits stabilize while others remain plastic. However, the literature on maturational changes in the brain's capacity for experience-dependent plasticity is primarily based on experiments in animals that mature over dramatically different time-scales than humans. Moreover, while principles of plasticity for sensory and motor systems might be conserved across species, the myriad of late-developing and uniquely human cognitive functions such as literacy cannot be studied with ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…White matter abnormalities have been observed in children with reading difficulties, most often in left temporo-parietal white matter [11][12][13][14] as language and reading networks are typically left lateralized [11,15,16]. Finally, changes in DTI measures are observed in reading-related white matter following reading interventions [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…White matter abnormalities have been observed in children with reading difficulties, most often in left temporo-parietal white matter [11][12][13][14] as language and reading networks are typically left lateralized [11,15,16]. Finally, changes in DTI measures are observed in reading-related white matter following reading interventions [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…So far, a few meta-analyses of EF training studies in children and adolescents have found no age effects (Sala & Gobet, 2020;Scionti et al, 2019), raising the possibility that there may not be a clear overall younger age benefit as previously suggested. In the academic domain, complex reading interventions may show plasticity over wider age ranges than previously thought (Yeatman & Huber, 2019). On the other hand, in studies that individually targeted skills like phonological awareness, there is some evidence from meta-analyses for a benefit to intervening at early grade levels (Bus & Van Ijzendoorn, 1999;Ehri et al, 2001), while interventions for more complex abilities, like reading comprehension, become more important later on (Suggate, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…One notable study directly examined the impact of an intensive reading intervention program on white matter plasticity changes in 7-to 13-year-olds with dyslexia or parent-reported reading difficulties (Yeatman & Huber, 2019). The intervention consisted of 8 weeks of the Seeing Stars program, which focuses on training orthographic and phonological processing skills.…”
Section: Neuroimaging Studiesmentioning
confidence: 99%
“…Limitations of this study included its sample of only third and fourth graders (M = 8.82). Although this did not allow for the examination of sex differences in white matter development over time in these children, it is important to note that this age represents a point of critical development, particularly in terms of language and reading [ 85 , 86 ]. It is still important to note that the differences observed in this age group may change over time with continued brain and reading skill development, which might alter sex differences.…”
Section: Discussionmentioning
confidence: 99%